Pushing On-Chip Photosensitivity Forward Using Edge-Driven Vertical Organic Phototransistors - Maria de Andrade, Denise [UNESP]; Merces, Leandro; Nawaz, Ali; Bof Bufon, Carlos Cesar [UNESP] (American Chemical Society (ACS), 2023)
Developing high-performance photosensors using prototype device architectures is essential to pushing forward developing and advancing next-generation optoelectronic applications. This work reports an organic phototransistor (OPT) with an ultra-short conducting channel (tens of nanometers) and outstanding photoelectric conversion efficiency. The OPT is based on a vertical organic field-effect transistor (VOFET) architecture, which utilizes a rolled-up metallic nanomembrane (NM) as the drain electrode and a photolithographically patterned (rectangular-shaped) perforated source electrode. These features expand the concept of conventional VOFETs as the former enables the incorporation of ultra-thin active layers and allows reliable control over gate-induced modulation of channel current. Using the engineering as abovementioned strategies, we focused on obtaining an improved device performance, studying their fundamental operating principle, and further investigating their application as photosensors. The optimized devices exhibited low operating voltages (<5 V) and enhanced on/off current ratio (∼105). The VOFET photoresponse was characterized by measuring the electrical characteristics in the dark and under illumination using three different monochromatic light colors. Under blue light, our devices demonstrated impressive photosensitivity (Pmax ≈ 105) and fast photoelectric conversion (steep light-induced threshold voltage shift), demonstrating that the rolled-up NM OPT shows excellent potential as a highly sensitive photodetector with low power consumption.
Keywords: DNTT; organic phototransistor; patterned source; photosensor; rolled-up nanomembrane; VOFET